The Colorblind Crowd? Founder Race and Performance in Crowdfunding - Younkin, Peter; Kuppuswamy, Venkat (Management Science, 2018)
The dearth of minority entrepreneurs has received increasing media attention but few academic analyses. In particular, the funding process creates challenges for either audit or correspondence methods, making it difficult to assess the role, or type, of discrimination influencing resource providers. We use a novel approach that combines analyses of 7,617 crowdfunding projects with an experimental design to identify whether African American men are discriminated against and whether this reflects statistical, taste-based, or unconscious bias on the part of prospective supporters. We find that African American men are significantly less likely than similar white founders to receive funding and that prospective supporters rate identical projects as lower in quality when they believe the founder is an African American male. We conclude that the reduction in perceived quality does not reflect conscious assumptions of differences in founder ability or disamenity but rather an unconscious assumption that black founders are lower quality. In two additional experiments, we identify three means of reducing this bias: through additional evidence of quality via third-party endorsements (i.e., awards, evidence of prior support), through evidence that African American founders have succeeded previously, and by removing indicators of the founder’s race. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2774 . This paper was accepted by Toby Stuart, entrepreneurship and innovation.